2010
DOI: 10.1136/gut.2010.217976
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for neuroinflammation and neuroprotection in HCV infection-associated encephalopathy

Abstract: As the increase of choline, creatine and myo-inositol are usually interpreted to indicate glial activation and macrophage infiltration in chronic inflammation and slow virus infections of the brain the present data endorse the hypothesis, that HCV infection may induce neuroinflammation and brain dysfunction. The concomitant increase of NN and the negative correlation to the extent of fatigue suggest a cerebral compensatory process after HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
3
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 45 publications
(48 reference statements)
8
98
3
10
Order By: Relevance
“…Few of the HCV patients with severe fatigue also complain of sleep disturbances, restless leg syndrome, muscle and joint pain, and depression. A recent study of 53 HCVpositive patients with neuropsychiatric has shown an increase choline and myoinositol concentrations in the basal ganglia and white matter, and an increase in the concentration of creatinine, Nacetylaspartate (NAA), and Nacetyl aspartylglutamate in basal ganglia [58] , these findings are consistent with the HCVinduced chronic cellular inflammation. Another study revealed an increased ratio of choline/creatine (Cho/Cr) in the basal ganglia as well as the frontal white matter of HCV infected patients through magnetic resonance spectroscopy [59] .…”
Section: Mechanisms Contributing To Neurological Dysfunctionsupporting
confidence: 77%
“…Few of the HCV patients with severe fatigue also complain of sleep disturbances, restless leg syndrome, muscle and joint pain, and depression. A recent study of 53 HCVpositive patients with neuropsychiatric has shown an increase choline and myoinositol concentrations in the basal ganglia and white matter, and an increase in the concentration of creatinine, Nacetylaspartate (NAA), and Nacetyl aspartylglutamate in basal ganglia [58] , these findings are consistent with the HCVinduced chronic cellular inflammation. Another study revealed an increased ratio of choline/creatine (Cho/Cr) in the basal ganglia as well as the frontal white matter of HCV infected patients through magnetic resonance spectroscopy [59] .…”
Section: Mechanisms Contributing To Neurological Dysfunctionsupporting
confidence: 77%
“…We recently found MRS markers of neuroinflammation to be increased in HCV patients with only mild neuropsychiatric symptoms in contrast to those with severe symptoms, suggesting a neuroprotective effect of the inflammatory response [2]. Thus, our findings are in contrast to the conclusion drawn by Byrnes et al, who hypothesize that their MRI results reflected reduced neuroinflammation as a consequence of HCV eradication and that reduced neuroinflammation caused the improvement of the psychometric test results observed in their patient group.…”
Section: To the Editorcontrasting
confidence: 86%
“…Patients infected with HCV showed elevated Cho, Cr, and mIns compared to healthy controls and those with hepatitis B, which may be due to microglial activation. Those cerebral metabolite abnormalities were independent of HE (Bokemeyer et al 2011;Chang et al 2013), indicating neuronal damage was mainly due to the HCV infection (Bladowska et al 2013;Chang et al 2013).…”
Section: General Application By Mr Imaging Of Neuroinflammation In Hementioning
confidence: 97%